Academic Senate Minutes 2007-11-29 - Academic Senate:::::::::
Agenda amended and approved. Approval of Minutes of 9/27/07 approved. Revision of the CALS program approved. Associated Student Report. Minor in Paleontology – Approved. Revision to Grade Appeal Procedures – First Reading. Update on WASC. Provost Report. Sustainability Resolution – First Reading. Focus the Nation first reading waived, but time certain reached before vote could be taken. Statewide Senator Report. Ad-Hoc Committee – CIHS continued. Remarks by Chief Financial Officer, L. Furukawa-Schlereth.